Multimodal size distribution of Si nanoclusters in SiO₂ as manifestation of interaction in the space of sizes - Blonskiy, I.V.; Lev, B.I.; Valakh, M.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
This paper summarizes the results of experimental studies revealing a multimodal character of the function of size distribution of Si nanoclusters in light-emitting SiO₂:Si structures. To explain the nature of this multimodality, a “liquid” approach to the description of the coalescence stage based on taking into account the correlation effects caused by particle-particle interactions in the space of sizes is proposed. This approach is justified by a high concentration of solutions where the nuclei of the new phase are described by a multimodal function of size distribution. Узагальнені результати експериментальних досліджень, які засвідчують полімодальність функції розмірного розподілу кремнієвих наночасток в матриці SiO₂ в випадку сильного перенасичення розчину SiO2:Si кремнійовою компонентою. Для пояснення природи полімодальності запропоновано «рідинний» підхід в описі стадії коалесценції, який оснований на врахуванні процесів міжчастинкової взаємодії в просторі розмірів. Запропонований підхід може виявитись перспективним для розвитку фізичних основ керування спектральним складом і інтенсивністю випромінювання кремнійових випромінювачів світла. Обобщены результаты экспериментальных исследований, свидетельствующие о полимодальности функции размерного распределения кремниевых наночастиц в матрице SiO₂ в случае сильного пересыщения раствора SiO2:Si кремниевой составляющей. Для объяснения природы полимодальности предложен «жидкостный» подход в описании стадии коалесценции, основанный на учете процессов межчастичного взаимодействия в пространстве размеров. Предложенный подход перспективен для развития физических принципов управления спектральным составом и интенсивностью излучения кремниевых излучателей света.